Studies on an iron(iii)-peroxo porphyrin. Iron(iii)-peroxo or iron(ii)-superoxo? - Dürr, Katharina L.; Olah, Julianna; Davydov, Roman; Kleimann, Michael; Li, Jing; Lang, Nina; Puchta, Ralph; Hübner, Eike; Drewello, Thomas; Harvey, Jeremy N.; Jux, Norbert; Ivanovic-Burmazovic, Ivana (Dalton Transactions, 2010)
We demonstrate that a one electron reduced product of the heme iron dioxygen adduct exists in solution not only as the commonly accepted iron(iii)-peroxo species, but coexists with its isomeric iron(ii)-superoxo form. This unusual reduced metal-superoxide adduct [M(ii)-O] is recently reported as a reactive intermediate in the case of non-heme extradiol dioxygenases and could also be generated by cryoreduction of a heme Fe-O adduct. The existence of iron(ii)-superoxo species in solution is consistent with IR, EPR, mass and Mössbauer spectra. The equilibrium between heme iron(iii)-peroxo and iron(ii)-superoxo forms is supported by density functional theory and explains our previous finding that upon release of coordinated (su)peroxide a corresponding iron(ii) complex remains. These results shed new light on the nature of heme iron(iii)-peroxo species that are key intermediates in the metalloenzyme-catalyzed dioxygen and hydrogen peroxide activation. © 2010 The Royal Society of Chemistry.